Moisture modulated refractive index difference of engineered pore interface for indoor temperature and humidity regulation - Guo, Yang (2024)
Regulation of indoor environments like temperature and humidity consumes enormous energy and brings environmental crises. Therefore, the development of energy-free approaches is critical as it simultaneously improves living comfort and decreases the carbon footprint. Here we report a moisture-modulated strategy to access switchable thermal regulation by tuning solar radiative scattering through manipulation of the refractive index difference (Δn) of a porous surface. This approach is based on a double-layered film containing an upper porous polymer layer and a lower photothermal layer. Via moisture absorption and evaporation, the film performs a reversible thermal switching between solar heating and radiative cooling, allowing efficient space temperature manipulation in the range from + 12.0 to − 8.0 °C. Besides, the moisture-modulated characteristic also offers an opportunity for solar dehumidification by automatically absorbing ambient moisture while mitigating temperature rise. This work bridges a thermal nexus between moisture with solar radiation, while providing a guideline for energy-free indoor environment manipulation.